Innovative Design of Novel Main and Secondary Arch Collaborative Y-Shaped Arch Bridge and Research on Shear Lag Effect of Its Unconventional Thin-Walled Steel Box Arch Ribs - Qian Huang; Xiaoguang Wu; Hui Wei; Qida Chen (Applied Sciences, 2022)
The first main and secondary collaborative Y-shaped steel box arch bridge under construction in China is a rarely seen innovative practice among bridges already built at home and abroad, which is an attractive engineering research topic in the field of advanced bridge design and construction, and the investigation of this bridge has made a groundbreaking contribution. The structure of unconventional thin-walled steel box arch ribs is very novel, abandoning the traditional two-dimensional arch rib structure form and adopting the new structural mode of single–double combination and joint working of main and secondary arches. However, for this innovative design, many technical difficulties including innovative design details, mechanical behavior of thin-walled structures and construction methods still need to be pioneeringly explored and thoroughly researched. In this paper, the innovative design concept of unconventional thin-walled arch ribs for spatial Y-shaped steel box arch bridges is described, and a comparative analysis with the corresponding conventional single arch rib structure is carried out. Due to the limitations of the common conventional arch bridge research methods, a combined global and local finite element method is used to analyze the static and dynamic properties of the structure, and the shear lag effect of the thin-walled steel box arch ribs is studied in a pioneering and exploratory approach. In addition, the stress distribution of the bifurcated section of the arch ribs and the configuration of the diaphragm are analyzed in detail to verify the reasonableness, advantage and applicability of the innovative design. The results show that the main and secondary arch collaboration Y-shaped steel box arch bridge has reasonable structure and superior mechanical properties and has a greater value for promotion The design concept and analysis method are worthy of use as a reference for the aesthetical and mechanical design of similar spatial Y-shaped arch bridges in the future.